(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of scientific research activities, and analyze influencing factors at Trung Vuong Hospital, Ho Chi Minh City during the period 2019-2024. Subject and method: Mixed-method research combining quantitative and qualitative approaches. Collecting data on the current state of scientific research through a survey of 316 healthcare workers and examined research records from 2019-2024. Influencing factors were explored through eight in-depth interviews and four focus group discussions. Results: There were 55 research projects, and 14 scientific publications during the period 2019-2024, 64.3% of which were published in domestic journals. Mean age of participants was 36.6±9.2 years, and 71.5% were females. The rate of participation in scientific research is 38.9%. Furthermore, there was a statistically significant difference between age, educational attainment, work unit, and position, and the status of participation in scientific research (p<0.05). Factors influencing scientific research were categorized based on the WHO six building blocks, including: health workforce, information systems, technology/ infrastructure/ equipment, financing, organization and management, and service delivery. Conclusion: Scientific research activities at Trung Vuong Hospital in the period 2019-2024 have shown a decreasing trend. Influencing factors on the scientific research landscape stem directly from the six core functional aspects of the health system delineated by the WHO. Trung Vuong Hospital should establish a dedicated scientific research management department and develop a comprehensive database system to enhance the efficiency of management, accessibility, and implementation for healthcare professionals.